2014
DOI: 10.4028/www.scientific.net/msf.783-786.2816
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Effect of the Interpass Temperatures in Properties and Microstructures of the Alloy 625 Dissimilar Fusion Zone

Abstract: The purpose of this study is to evaluate the effectiveness in the contribution of the interpass welding in the microstructures and properties of the dissimilar fusion zones produced with an alloy 625 and API 5L X65 steel pipes. Three multipass welded joints with v-groove, were made under the same welding parameters, therefore, changing only the interpass temperatures at: 150°C, 250°C and 450°C. The microstructural characterization was performed using the light microscopy and the scanning electron microscopy (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Notwithstanding Also for 100 and 200 h of exposure at 650 °C the presence of large blocks of NbC carbides and cubic NbTi complex were found, which remained from solidification. However, these particles probably have low or no effect on toughness, since in another study, carried out by Silva et al [48][49] evaluating the effect of the interpass temperature on mechanical properties in weld metal of 625 alloy, these particles were found. The results of the Charpy-V impact test at cryogenic temperature (-196 °C) showed no significant differences among the weld conditions and the level of energy absorbed was higher than 100 J.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Notwithstanding Also for 100 and 200 h of exposure at 650 °C the presence of large blocks of NbC carbides and cubic NbTi complex were found, which remained from solidification. However, these particles probably have low or no effect on toughness, since in another study, carried out by Silva et al [48][49] evaluating the effect of the interpass temperature on mechanical properties in weld metal of 625 alloy, these particles were found. The results of the Charpy-V impact test at cryogenic temperature (-196 °C) showed no significant differences among the weld conditions and the level of energy absorbed was higher than 100 J.…”
Section: Discussionmentioning
confidence: 96%
“…It is possible that this was due to the formation of the orthorhombic  phase. Another works [49][50] has found that a reduction in Charpy impact energy to around 180 to J/cm 2 occurred as a result of intermediate temperature ageing, which was attributed primarily to the formation of the orthorhombic  phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation